Approaching Resilient Cities through Social-Ecological Connectivity: A Spatial Analysis of Amman City Center, Jordan - Alshafei, Islam; Righelato, Pinar Ulucay (VDE VERLAG GMBH, 2025)
The built environment, which encompasses natural and complex systems known as urban communities, faces various multifaceted challenges. While resilience has long been a central focus in disaster risk reduction (DRR) studies and practices, there remains an urgent need for innovative approaches to building resilience from a socio-ecological systems (SES) perspective. This calls for developing new tools to assess urban communities' social and ecological components. Research within the SES framework highlights the interdependence of these systems. Therefore, promoting resilience in urban environments requires strengthening the resilience capacities of both social and ecological systems. This study adopts a case study approach, integrating tools from space syntax and graph map theories to evaluate the connectivity of social and ecological networks. It proposes strategies to reduce vulnerabilities and enhance resilience within a socio-ecological systems framework. © 2025, VDE VERLAG GMBH. All rights reserved.
Keywords: Connectivity Spatial Analysis; Depth Map Analysis; Graph Theory; Linkage Mapper Analysis; Resilient Cities; Social-Ecological Systems (SES); Space Syntax Theory